Analysis of Student Needs for the Development Video Demonstration of Science Practicum with Critical Thingking Orientation on Temperatur and its Changes - Dwi Utari Savenny; Arief Muttaqiin (Universe, 2023)
This study aims to conduct a preliminary study on the analysis of the needs of junior high school students for the development of a video demonstration of science practicum oriented to critical thinking on temperature and its changes. This research was conducted using the Plomp development model which consists of three stages including preliminary research (initial investigation stage), prototyping stage (prototype formation), and assessment phase (assessment stage). In this article, it only explains the analysis of students who are at the preliminary research stage. This preliminary study research was conducted by class VII.2 totaling 32 students by distributing questionnaires. The results of the data obtained were that almost all students as subjects were interested in the science practicum demonstration video.